Pengaruh Penambahan Silica Nanopartikel dan Surfaktan SLS (Sodium Lignosulfonat) terhadap Proses Adsorpsi pada Enhanced Oil Recovery (EOR) - Handayani, Destias Selly; Yuliansyah, Ahmad Tawfiequrrahman; Purwono, Suryo (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Surfactant flooding is a chemically enhanced oil recovery (EOR) technique that removes trapped residual oil by lowering the oil-water interfacial tension. The success of surfactant flooding is strongly affected by surfactant loss through its adsorption process on reservoir mineral rocks. Surfactant adsorption is a test method to determine whether surfactant is adsorbed in the reservoir rocks. In the surfactant adsorption test, only static adsorption was carried out. The mixed-surfactant formulation used 70% surfactant SLS, 22% PFAD, and 8% 1-octanol (w/v). Mixed-surfactant concentration variations are 0.25, 0.5, 0.75, and 1% (w/v). The IFT test results showed that the smallest IFT value at a concentration of 1% is 3.15 x 10-3 mN/M. In this research, adding silica nanoparticles (SNPs) to the mixed-surfactant solution is expected to reduce the interfacial tension (IFT) value and the amount of surfactant adsorbed in the reservoir rocks. Variations of SNPs concentration used are 0.05, 0.09, 0.15, and 0.3% (w/v). The lowest IFT test result by adding concentration SNPs of 0.09% is 2.07 x 10-4 mN/M. The adsorption test result showed that by adding SNPs with concentration 0.09%  with adsorption time of 24h is effective to used for adsorption.